Development innovation of silver nanoparticles used leaves of banana (Musa sapientum) as eco-friendly bioreductor - Bambang Hernawan Nugroho; Rika Artikawati; Suparmi Suparmi (Jurnal Ilmiah Farmasi, 2021)
Abstract Background: Silver nanoparticle could be developed by natural reducing agent like Epigallocatechin Gallate (EGCG) of banana leaves (Musa sapientum) as bioreductor in biosynthesis.Objective: This study aimed to examine the formulation and characterization of silver nanoparticles using the combination of banana leaf (M. sapientum) extract containing epigallocatechin gallate (EGCG) for biosynthesis. The biosynthesis of silver nanoparticles is eco-friendly and low energy process.Method: Each formula was added with 500microlitre AgNO3. Identification of nanoparticles was characterized by duration of its discoloration, its absorbance using UV/Vis spectrophotometer and FTIR, its particle size using PSA, and its morphology under TEM.Result: The silver nanoparticle formation need less than 15 minutes. The measurement of its absorbance showed the wavelength of this silver nanoparticles are in the range of 410-480nm. Characterization using FTIR showed a decrease in absorption of the functional -OH group spectrum. This particle has the smallest particle size in value of 57.16 ± 0.40 nm in spherical shape.Conclusion: Nanosilver could be prepared using banana leaf extract using low energy biosynthesis process.Keywords: characterization, nanosilver, banana leaf (M. sapientum) Intisari Latar belakang: Nanopartikel perak dapat dihasilkan melalui bahan pereduksi dari alam yang mengandung  epigallocatechin gallate (EGCG) yang terdapat pada daun pisang (Musa sapientum) sebagai bioreduktor.Tujuan: Penelitian ini bertujuan untuk membuat formulasi dan karakterisasi nanopartikel perak menggunakan kombinasi ekstrak daun pisang (M. sapientum) yang mengandung EGCG.Metode: Masing-masing formula ditambahkan dengan 500mikrolitre AgNO3. Kemudian dilakukan Identifikasi dan karakterisasi nanopartikel dengan melihat parameter perubahan warna, spektrofotometri UV-Vis dan FTIR, pengamatan partikel dengan PSA dan pengamatan morfologi partikel dengan TEM.Hasil: Hasil pengamatan menunjukkan bahwa terjadi perubahan warna kurang dari 15 menit setelah pencampuran. Hasil pengukuran pada UV-Vis spektrofotometer memiliki resonasi permukaan plasmon pada daerah 410-480 nm. Karakterisasi menggunakan FTIR menunjukkan penurunan penyerapan spektrum gugus -OH fungsional. Ukuran partikel terkecil yang diperoleh yaitu pada 57,16±0,40 nm dan berbentuk sferis. Kesimpulan: Nanopartikel perak dapat dibuat dengan menggunakan ekstrak daun pisang melalui proses biosintesis rendah energi.Kata kunci: karakterisasi, nanopartikel perak, daun pisang (M. sapientum)